PENGARUH TERAPI BEHAVIORAL TERHADAP INKONTINENSIA URIN PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA - Arsihak, Muhammad; Lina, Liza Fitri (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2023)
The aging process will occur with age so that it has an impact on aspects of life, both social, economic and health. Aging causes health problems in the elderly with physiological changes in organ systems due to degenerative processes and a decrease in the immune system that occurs in old age. Health problems that often arise such as: intellectual decline / dementia, depression, decreased endurance, sleep disturbances and urinary incontinence. Urinary incontinence is a decrease in the resistance of the striated muscles in the urethra causing neurological dysfunction which causes loss of control over urination. The purpose of this study was to determine the effect of behavioral therapy on urinary incontinence in the elderly at Tresna Werdha Social Institution, Bengkulu City. This type of quantitative research with Quasi Experiment method with one group pretest posttest design. The results showed that urinary incontinence before behavioral therapy intervention was 4.87 with SD = 0.915, while the average frequency distribution of urinary incontinence after behavioral therapy intervention was 6.80 with SD = 0.561. The conclusion is that there is a significant effect between before and after behavioral therapy on urinary incontinence in the elderly at Tresna Werdha Social Institutions in Bengkulu City with a p-value of 0.001 <0.005. Suggestions for future researchers can research interventions with behavioral therapy with relaxation techniques that can reduce urinary incontinence.